Pengembangan Media Komik Digital pada Materi Sistem Hormon untuk Meningkatkan Hasil Belajar Siswa Kelas XI - Joko Andi Susilo; Evi Hanizar; Hanif Rafika Putri (JOEAI (Journal of Education and Instruction), 2025)
This research aims to develop and test the feasibility of learning media in the form of digital comics on the hormone system material for class XI as a supporting tool in biology learning. This research uses the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The media was validated by two experts, namely material experts and media experts, with validity results of 97% and 90%, respectively, which fall into the very feasible category. Trials were conducted at two schools, namely MA Raudatul Ulum and MA Miftahul Ulum, with 27 students each. Cognitive learning outcomes were analyzed through pretest and posttest, which showed a significant improvement. At MA Raudatul Ulum, the average posttest score reached 84 with a completeness rate of 92%, while at MA Miftahul Ulum, it reached 83 with a completeness rate of 88%. These results indicate that digital comic media is effective in improving students' understanding of hormone system material. Thus, this media can be an alternative solution in biology learning that is more engaging and interactive.   Keywords: Digital Comics, Hormone System, Learning Outcomes